The Political Economy of Poverty, Vulnerability and Disaster Risk Management : Building Bridges of Resilience, Entrepreneurshi. - Mawere, Munyaradzi (Oxford : Langaa RPCIG, 2017)
Poverty remains a thorny and topical challenge and research topic to scholars and researchers on African development. Scholars in the Global North have since the Second World War sought to research poverty and underdevelopment in Africa, postulating what they think are the major causes of insipid and abject poverty in the continent, but with little or no success on how to solve the poverty enigma. Sadly, little research and homework have been done by scholars in context (in Africa) on why there seems to be more production rather than eradication of poverty and vulnerability in Africa and among Africans. This book is born out of the realisation for the need for both scholars on the ground and outside Africa to earnestly interrogate and reflect on the poverty situation that continues to haunt the people of Africa and rattle the conscience of the world at large. With contributors from across the continent and beyond, the volume offers a balanced and rigorous, multi-faceted analysis of Africa's poverty and vulnerability from a rich tapestry of perspectives. The volume is handy to scholars and students in the fields of African and development studies, as well as to students of Sociology, Anthropology, Political Science and Policy Studies.
1. Poverty and vulnerability in Africa : reversing the losses and capitulating on the gains / Munyaradzi Mawere -- 2. The political economy of poverty and vulnerability : how Africa can break the cycle of poverty to unlock its underdevelopment jam? / Munyaradzi Mawere -- 3. Poverty and the discourses about the global north's playing of the global south / Nkwazi Mhango -- 4. Breaking the cycle of poverty : rethinking Africa's socio-political economy / Aluko Idowu Opeyemi & Munyaradzi Mawere -- 5. Resorting to illegality : the illicit Shangwe cannabis trade as an anti-cotton response to agrarian policy in colonial Zimbabwe, c. 1962-1979 / Simeon Maravanyika & Harro Maat -- 6. Political naivety, corruption, and poverty promotion in Africa : riding the 'poorest-ugliest French' bijuralism horse from Cameroon to Canada via Britain / Peter Ateh-Afac Fossungu -- 7. Poverty and environmental degradation on a large scale : the history of the establishment, operation and management of a multinational mining enterprise at Mashava, 1903-2015 / Davidson Mabweazara Mugodzwa -- 8. Ethnographic monitoring through phone-in radio programs : an example from Ankore, Uganda / Clementia Murembe Neema, Jenny-Louise Van der Aa, Sjaak Kroon & Veerle Draulans -- 9. Fighting fellow comrades in the trenches of poverty in Africa? Interrogating the fees must fall movement at the University of Namibia and universities in South Africa / Artwell Nhemachena & Romeo Mudimu -- 10. The impoverished African and the poverty of colonially inherited education in Africa / Ephraim Taurai Gwaravanda -- 11. Children, women, development and fundamental human rights in some African societies / Muhammed A. Yinusa; Joseph A. Oluyemi & Raji Abdullateef -- 12. Community engagement for development and poverty alleviation in rural Zimbabwe : a case study of Chikunguwo community gardening in Bikita / Costain Tandi & Munyaradzi Mawere -- 13. Seeing beyond national borders : impoverished visually-impaired Zimbabwean beggars in Johannesburg, South Africa / Fidelis Peter Thomas Duri & Eusebiah Chikonyora -- 14. Disasters, the marginalised and media preparedness in Zimbabwe : reflections on the Masvingo-based community media organisations' coverage of the 2017 Cyclone Dineo victims / Golden Maunganidze & Munyaradzi Mawere.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Emergency management; Economic development -- Africa; Poverty -- Africa; Africa -- Economic conditions; Développement économique -- Afrique; Pauvreté -- Afrique; Afrique -- Conditions économiques.; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Poverty & Homelessness; Economic development; Economic history; Emergency management; Poverty; Africa